Sphingosine‐1‐phosphate/TGF‐β axis drives epithelial mesenchymal transition in asthma‐like disease. (21st January 2022) - Riemma, Maria A.; Cerqua, Ida; Romano, Barbara; Irollo, Elena; Bertolino, Antonio; Camerlingo, Rosa; Granato, Elisabetta; Rea, Giuseppina; Scala, Stefania; Terlizzi, Michela; Spaziano, Giuseppe; Sorrentino, Rosalinda; et al.
Abstract : Background and Purpose: Airway remodelling is a critical feature of chronic lung diseases. Epithelial‐mesenchymal transition (EMT) represents an important source of myofibroblasts, contributing to airway remodelling. Here, we investigated the sphingosine‐1‐phosphate (S1P) role in EMT and its involvement in asthma‐related airway dysfunction. Experimental Approach: A549 cells were used to assess the S1P effect on EMT and its interaction with TGF‐β signalling. To assess the S1P role in vivo and its impact on lung function, two experimental models of asthma were used by exposing BALB/c mice to subcutaneous administration of either S1P or ovalbumin (OVA). Key Results: Following incubation with TGF‐β or S1P, A549 acquire a fibroblast‐like morphology associated with an increase of mesenchymal markers and down‐regulation of the epithelial. These effects are reversed by treatment with the TGF‐β receptor antagonist LY2109761. Systemic administration of S1P to BALB/c mice induces asthma‐like disease characterized by mucous cell metaplasia and increased levels of TGF‐β, IL‐33 and FGF‐2 within the lung. The bronchi harvested from S1P‐treated mice display bronchial hyperresponsiveness associated with overexpression of the mesenchymal and fibrosis markers and reduction of the epithelial.The S1P‐induced switch from the epithelial toward the mesenchymal pattern correlates to a significant increase of lung resistance and fibroblast activation. TGF‐β blockade, in S1P‐treated mice, abrogates these effects. Finally, inhibition of sphingosine kinases by SK1‐II in OVA‐sensitized mice, abrogates EMT, pulmonary TGF‐β up‐regulation, fibroblasts recruitment and airway hyperresponsiveness. Conclusion and Implications: Targeting S1P/TGF‐β axis may hold promise as a feasible therapeutic target to control airway dysfunction in asthma.